"Inhibitory effect of Brazilian red propolis on Candida biofilms developed on titanium surfaces" - Loyse Martorano-Fernandes; Yuri Wanderley Cavalcanti; Leopoldina de Fátima Dantas de Almeida (BMC, 2020)
Abstract Background Peri-implant inflammation resulting from the presence of Candida biofilms may compromise the longevity of implant-supported dentures. This study evaluated the inhibitory effect of Brazilian red propolis on mono-species biofilms of C. albicans (ATCC 90028) and co-culture biofilms of C. albicans (ATCC 90028) and C. glabrata (ATCC 2001), developed on titanium surfaces. Methods Titanium specimens were pre-conditioned with artificial saliva and submitted to biofilm formation (1 × 106 CFU/mL). After 24 h (under microaerophilic conditions at 37 °C) biofilms were submitted to treatment for 10 min, according to the groups: sterile saline solution (growth control), 0.12% chlorhexidine and 3% red propolis extract. Treatments were performed every 24 h for 3 days and analyses were conducted 96 h after initial adhesion. After that, the metabolic activity (MTT assay) (n = 12/group), cell viability (CFU counts) (n = 12/group) and surface roughness (optical profilometry) (n = 6/group) were evaluated. Data from viability and metabolic activity assays were evaluated by ANOVA and Tukey tests. Surface roughness analysis was determined by Kruskal Wallis e Mann Whitney tests. Results Regarding the mono-species biofilm, the cell viability and the metabolic activity showed that both chlorhexidine and red propolis had inhibitory effects and reduced the metabolism of biofilms, differing statistically from the growth control (p < 0.05). With regards the co-culture biofilms, chlorhexidine had the highest inhibitory effect (p < 0.05). The metabolic activity was reduced by the exposure to chlorhexidine and to red propolis, different from the growth control group (p < 0.05). The surface roughness (Sa parameter) within the mono-species and the co-culture biofilms statistically differed among groups (p < 0.05). Conclusions Brazilian red propolis demonstrated potential antifungal activity against Candida biofilms, suggesting it is a feasible alternative for the treatment of peri-implantitis.